Avaliação do desempenho e níveis de proteção sorológica em terneiros vacinados contra tristeza parasitária bovina (TPB) comparados aos naturalmente infestados por carrapatos - Arteche, Álvaro Carlos Menezes (2011)
This study analyzed, by reaction to indirect immunofluorescence and individual weighting, the levels of protection and weight-gain in beef calves from birth to the age of eight month, which received two doses of vaccine against tick fever and were maintained free from ticks, compared to naturally infested calves in extensive management conditions with continuous grazing in a rural property situated in the municipality of Santana do Livramento Espinilho / RS. Two groups were randomly gathered, n=30, from which Group I (test) was kept free from ticks from birth to weaning and received two doses of the attenuated, trivalent, refrigerated vaccine against tick fever. Groupe II (control) followed the property s traditional management, which reflects the one used in the region, allowing the tick infestation by the animals. Weight control was accomplished in the first day (d0) and in the last day of the experiment (d180). The serology revealed that 100% of the vaccinated animals presented titles equal to 1:5120 for the three parasites Anaplasma marginale, Babesia bovis e Babesia bigemina (p≤0,025), whereas in the control group the highest titles were 1:2560 in four animals for A. marginale, 1:1280 in four animals for B. bovis and 1:1280 in two animals for B. bigemina (p≤ 0,025). Group I got a mean weight-gain of 30,5 kg more than the control group at the end of the experiment (p≤0,025). The results obtained show that keeping animals free from tick, from birth to weaning, and maintaining them vaccinated against tick fever is safer, more efficient and economically and technically more advantageous than the traditional management system carrapateamento (natural tick infestation).